2018
DOI: 10.1002/jbm.a.36402
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effect of submicron porous and smooth ultrafine‐grained Ti‐20Mo surfaces on osteoblast responses

Abstract: The surface of an orthopaedic implant plays a crucial role in determining the adsorption of proteins and cell functions. A detailed comparative study has been made of the in vitro osteoblast responses to coarse-grained (grain size: 500 μm), ultrafine-grained (grain size: 100 nm), coarse-porous (pore size: 350 nm), and fine-porous (pore size: 155 nm) surfaces of Ti-20Mo alloy. The purpose was to provide essential experimental data for future design of orthopaedic titanium implants for rapid osseointegration. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…After culturing for 48 h, osteoblasts on laser-treated surfaces displayed round morphology with limited spreading ( Figure 4 c). This finding is consistent with a number of studies showing that no matter what cell types are used, cell spreading is hindered by topographical features on surfaces with convex or concave particles [ 65 ]. Another important observation was that in untreated samples, the cells grown on the surface were not randomly distributed.…”
Section: Discussionsupporting
confidence: 92%
“…After culturing for 48 h, osteoblasts on laser-treated surfaces displayed round morphology with limited spreading ( Figure 4 c). This finding is consistent with a number of studies showing that no matter what cell types are used, cell spreading is hindered by topographical features on surfaces with convex or concave particles [ 65 ]. Another important observation was that in untreated samples, the cells grown on the surface were not randomly distributed.…”
Section: Discussionsupporting
confidence: 92%
“… 46 Moreover, it has been reported that pore features (size and depth) have a greater effect than smooth surfaces on cell growth and osteogenic capacity. 47 In our study, less new bone was regenerated in PEEK-300 although this scaffold exhibited higher bone-related gene expression in vitro at day 14, which indicated that the pore size of 300 μm may be more appropriate for earlier osseointegration, whereas the larger pore sizes of 450 and 600 μm supported more bone regeneration at a later stage. This may suggest that larger pore sizes (>300 μm) are more conducive to nutrient and oxygen exchange, which could promote the process of bone ingrowth and vascularization.…”
Section: Discussionmentioning
confidence: 49%
“… 14 , 16 , 17 , 19 , 23 , 44 , 46 , 47 , 49 Taken together, it becomes clear that increasing surface roughness and porosity not only increase the reactive surface area of the biomaterial, but more importantly that osteoblastic cells are able to detect surface topology on a wide nanometer scale range (tens to hundreds of nanometers), and will react differently, according to specific surface parameters. 12 , 14 , 15 , 24 , 44 , 46 , 47 , 49 While a large number of studies suggest that rough titanium surfaces offer a better implant performance compared to smooth titanium surfaces, in part because of their increased surface roughness, ultrahigh values of roughness (R a of 52–74 μm) are not correctly sensed by osteoblastic cells and thus are not compatible with optimal titanium implant performance. 12 , 14–17 , 19 , 23 , 42 , 43 , 54 , 55 Interestingly, osteoclasts (bone-degrading cells), were found to react to smooth and rough titanium surfaces similarly to osteoblasts.…”
Section: Discussionmentioning
confidence: 99%